Influence of Ce substitution in LaMO3 (M = Co/Ni) perovskites for COx-free hydrogen production from ammonia decomposition - Seetharamulu Podila (Elsevier, 2022)
The La based perovskite type LaMO3 (M = Ni, Co) oxides were prepared by combustion synthesis method using citric acid as organic fuel. These catalyst precursors tested for ammonia decomposition. The LaNiO3 and LaCoO3 catalysts showed good activity for NH3 decomposition. The LaNiO3 catalyst displayed greater activity than LaCoO3. This due to high surface area and easily reducibility of Ni species. A 50% of La was substituted by Ce in both LaNiO3 and LaCoO3 catalysts. A remarkable effect on catalytic performance was observed with the partial substitution of La by Ce in perovskite catalyst especially at lower temperatures. The La0.5Ce0.5NiO3 catalyst exhibited highest activity among all prepared samples. The achieved superior activity is due to boost in surface area, reducibility and suitable basicity. The SEM elemental mapping of La0.5Ce0.5NiO3 catalyst concluded that metal oxide constituents dispersed homogeneously. The La0.5Ce0.5NiO3 catalyst showed excellent stable catalytic performance during 50 h time on study at 550 °C.